Agro-Ecological Assessment of Lands in Behshahr County for Lentil (Lens culinaris Medik.) Cultivation - Karim Reyahi; Hossein Kazemi; Afshin Soltani; Fardin Sadeghzadeh (بوم شناسی کشاورزی)
Introduction Agriculture is one of the most important economic sectors of the country, and it plays a vital role in achieving sustainable development, which requires the use of scientific principles and methods and the recognition of environmental capabilities. In this regard, there is a close relationship between agricultural development and environmental resources. In recent years, the level of agricultural land has decreased, and this decrease in land suitable for agricultural production can be attributed to the lack of optimal land use, which has directly affected the ability to produce food on a large scale and seriously affected food security. However, in many cases, agricultural systems have low production, which is related to management issues. Also, the climatic capabilities of the regions are sometimes effective as a limiting factor in crop production. Based on this, it is very important to identify the capabilities of the land before the performance of various activities such as agriculture. This study was carried out with the aim of agroecological evaluation of lands in Behshahr County (Yane-Sar region) for lentil cultivation using spatial analysis of geographical information system (GIS) and analysis hierarchy process (AHP) in 2021-2022. Materials and Methods This research was carried out in the agricultural lands of the Yane-sar district of Behshahr county in Mazandaran province from 2021 to 2022. In order to prepare digital maps of soil characteristics of agricultural lands, agricultural soil samples were taken after the harvest in the summer of 2021. In this research, climatic variables (minimum, maximum, average temperatures and annual precipitation), topography (slope, aspect, and elevation above sea level), and soil characteristics (texture, K, P, Cu, Mn, N, Fe, TNV, organic matter, EC, pH) were used. Thematic maps for each variable were created using various models in ArcGIS 10.8 and then overlaid with AHP weights. The final map was classified into four categories: high suitability, suitability, semi-suitability, and non-suitability. Results and Discussion The results showed that the range of electrical conductivity (EC) in the soil of agricultural lands of the study area was between 0.84-2.63 dS m-1. According to its distribution, most of it is located in the northwest and southeast of the region, and its lowest value is located in the central and northern regions. Also, the results showed that the distribution of soil organic matter (OM) is between 0.35-7.22 percent. The central and southern areas of this region had the minimum percentage of organic matter. The results showed that the most suitable areas for lentil cultivation are located in the northern, central, and southern parts of the region. In general, two classes of high suitability and suitability comprise about 56.97% of the area. One of the main reasons for this result was the suitable soil fertility, rainfall, and topographical conditions. Zones with semi-suitability and non-suitability cultivation potential were also included in 43.03% of the region's area. The results showed that the northwest, parts of the centre, and parts of the southwest were located in the semi-suitability class for lentil cultivation.  Conclusion  Considering various factors to determine the suitable lands for lentil cultivation, it was found that most of the agricultural lands in the studied region were in zones of high suitability for lentil cultivation. Also, in the semi-suitability and non-suitability classes, low nitrogen amount in parts of the centre, high humidity and rainfall in the west of the region, high phosphorus amounts in parts of the central and northwest regions, the inappropriate texture in some fields and low rainfall were determined as limiting factors for the growth of lentil.